Efficacy and Safety of Proprotein Convertase Subtilisin/Kexin Type 9 Inhibitors as Adjuvant Treatments for Patients with Hypercholesterolemia Treated with Statin: A Systematic Review and Network Meta-analysis - Huang, Yi-Ting; Ho, Li-Ting; Hsu, Hsin-Yin; Tu, Yu-Kang; Chien, Kuo-Liong (Frontiers in Pharmacology, 2022)
Background: The proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors are potent LDL-C lowering agents. However, few head-to-head studies evaluated the efficacy on the lowering in other atherogenic apolipoproteins and safety of PCSK9 inhibitors at different dosages as an add-on statins therapy in hypercholesterolemia patients. Methods: This study is a systematic review and network meta-analysis of randomized control trials to compare the efficacy of lipid reduction and adverse events of PCSK9 inhibitors in statin-treated hypercholesterolemia patients. PubMed, EMBASE, and Cochrane Library databases were searched till April 20, 2021, for randomized controlled trials. Random-effect network meta-analyses were undertaken to compare the differences in the percent reduction in low-density lipoprotein cholesterol (LDL-C), apolipoprotein B (ApoB), and lipoprotein (a) [Lp(a)] levels and the risk of AEs among different PCSK9 inhibitors. Results: A total of 22 articles with 42,786 patients were included. The lipid reductions in LDL-C, ApoB, and Lp(a) with add-on PCSK9 inhibitors vs. placebo in statin-treated patients across all trials were 50–63%, 43–52%, and 23–31%, respectively. Evolocumab 140 mg Q2W was ranked the best among all treatment strategies for lowering LDL-C, ApoB, and Lp(a) levels, and the treatment difference was 68.05% (95% confidence interval (CI), 62.43% to 73.67) in LDL-C reduction, 54.95% (95% CI, 49.55% to 60.35%) in ApoB reduction, and 34.25% (95% CI, 27.59% to 40.91%) in Lp(a) reduction compared with the placebo. No significant risk difference of adverse events between PCSK9 inhibitors and placebo was found. Conclusion: PCSK9 inhibitors showed a significant effect on the reduction in LDL-C, ApoB, and Lp(a) levels in statin-treated patients. Evolocumab 140 mg Q2W showed significantly larger degrees of LDL-C, ApoB, and Lp(a) reduction.